Analysis of Financial Performance Before and After the Implementation of PSAK 73 on Leases in Transportation and Logistics Companies Listed on the Indonesia Stock Exchange from 2017 to 2022 - Salamah, Devi; Syafei, Jasmina; Yusrialis (MUI Kota Pekanbaru, 2025)
PSAK 73 is the latest accounting standard related to lease accounting adopted from IFRS 16. The implementation of PSAK 73 will become effective in 2020. The classification of finance leases is a type of lease that is permitted in PSAK 73 where the recognition, measurement, presentation and disclosure of right-of-use assets becomes more detailed in financial position reports. This research aims to analyze the impact of implementing PSAK 73 on rent on financial performance as seen by financial ratios. This research uses transportation and logistics sector companies as the research population. The sample selection method used a purposive sampling method and the companies that met the sample criteria were 15 companies. The analytical method used in this research is ratio analysis and statistical analysis using SPSS 23. The results of this research show that there is no significant difference in solvency ratios and profitability ratios between before and after the implementation of PSAK 73 on rents in listed transportation and logistics sector companies on the Indonesian Stock Exchange in 2017-2022.